Analysis of the Performance of Electronic Commerce in Ukraine - Kozlov, V. V.; Tomashevska, T. V. (Statistics of Ukraine, 2017)
The current phase in the development of economic relations is characterized by the high level of informatization. The rapid science & technology advancement in information and communication technologies pushes up the development of consumption, industry and trade, and lays the background for new forms of economic relations. Electronic commerce is an advanced area of business. Taking advantages from electronic trade, organizations can: considerably reduce financial and time resources, enhance competitiveness, enter new markets, obtain supplementary information on consumer needs, and rapidly respond on the changing demand. Many companies take advantage from electronic commerce and set up pre-sales and after-sales services. Today, the Ukrainian market of electronic commerce is undergoing rapid expansion. The objective of the study is to analyze the expansion dynamics of electronic commerce by Ukrainian region and find the latest tendencies in this industry. The analysis is made by statistical data on Internet use in Ukraine. The overall performance of electronic commerce in Ukraine lags far behind the analogous figures of Western countries. Negative effects of the economic crisis, lack of high performing telecommunication networks in a number of Ukrainian regions, and limited use of advanced electronic payment systems hampered the development of the electronic market in Ukraine, and still hamper it in some way. Yet, due to ICT solutions, the environment for electronic commerce, in which the increasing demand pushes up the supply, have recently been improved. The method for studying the electronic commerce performance by Ukrainian region by use of the dynamic personified matrix is proposed. On its basis the ranking of Ukrainian regions is built, the regions with the highest performance in electronic commerce are identified, performance trends are analyzed. It is found that the electronic commerce market is concentrated mainly in large cities that are regional centers. The reason behind is that provider firms and firms rendering hosting services are concentrated in large cities, whereas small towns and villages have no access to high quality connection. Therefore, the development of advanced telecommunications market is supposed to contribute to the expansion of the electronic commerce market, enabling to take full advantage from the Ukrainian potential in electronic trade and enhance the competitiveness of Ukrainian business.